Egypt’s experience bridging cash transfers and an economic inclusion program for sustainable social protection - Allen IV, James; Gilligan, Daniel O.; Kurdi, Sikandra; Yassa, Basma (International Food Policy Research Institute, 2024)
In 186 countries worldwide, cash transfer programs are the cornerstone of social protection, outnumbering social security or pension plans. These offer critical financial lifelines to vulnerable households, aiming to alleviate poverty by providing steady cash support. However, these programs can become long-term fiscal burdens for governments due to limited turnover of recipients, particularly when the programs do not lead to lasting reductions in poverty.